A mixed‐methods evaluation of stakeholder perspectives on pediatric pneumonia in Nigeria—priorities, challenges, and champions. Issue 1 (27th January 2020) - King, Carina; Iuliano, Agnese; Burgess, Rochelle Ann; Agwai, Imaria; Ahmar, Samy; Aranda, Zeus; Bahiru, Solomon; Bakare, Ayobami A.; Colbourn, Tim; Shittu, Funmilayo; Graham, Hamish; Isah, Adamu; et al.
Abstract: Background: Interventions to reduce pneumonia mortality exist; however, stakeholder engagement is needed to prioritize these. We explored diverse stakeholder opinions on current policy challenges and priorities for pediatric pneumonia in Nigeria. Methods: We conducted a mixed‐methods study, with a web‐survey and semi‐structured interviews, to explore stakeholder roles, policy barriers, opportunities, and priorities. Web‐survey participants were identified through stakeholder mapping, including researchers' networks, academic and grey literature, and "Every Breath Counts" coalition membership. Stakeholders included actors involved in pediatric pneumonia in Nigeria from non‐governmental, government, academic, civil society, private, and professional organizations. Stakeholder interviews were conducted with local government, healthcare managers, professional associations, and local leaders in Lagos and Jigawa states. Quantitative data were analyzed descriptively; qualitative data were analyzed using a thematic framework. Results: Of 111 stakeholders, 38 (34%) participated in the web‐survey and 18 stakeholder interviews were conducted. Four thematic areas emerged: current policy, systems barriers, intervention priorities, and champions. Interviewees reported a lack of pneumonia‐specific policies, despite acknowledging guidelines had been adopted in their settings. Barriers to effective pneumonia management were seen at all levels of the system, from the community to healthcare to policy, with key issues of resourcing and infrastructure. Intervention priorities were the strengthening of community knowledge and improving case management, focused on primary care. While stakeholders identified several key actors for pediatric pneumonia, they also highlighted a lack of champions. Conclusion: Consistent messages emerged to prioritize community and primary care initiatives, alongside improved access to oxygen, and pulse oximetry. There is a need for clear pneumonia policies, and support for adoption at a state level.